Evaluasi Responsivitas dan Akurasi Chatbot Menggunakan Algoritma Pencocokan Pola untuk Implementasi pada Perusahaan Menengah - Haeruddin, Haeruddin; Sabariman, Sabariman; Celvin, Celvin (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
This study aims to develop a website-based chatbot system using a matching pattern algorithm to improve the efficiency of the store department at PT.XYZ in managing warehouse inventory. The system is designed to assist users in adding item names, images, and quantities to the database in a more structured and efficient manner. The system development process was carried out using the SDLC method to ensure a systematic approach, while the performance of the developed features was tested using the black box testing method. The results of this study indicate that the web-based chatbot successfully displays item information based on user requests. Additionally, the system provides an option to add new items to the database if the requested item is not found, automatically updating the knowledge base with relevant string patterns. Black box testing results demonstrate that all key features, such as item search, quantity adjustment, and image display, function reliably and effectively. Thus, this chatbot system has proven to significantly support the operational efficiency of the store department at PT.XYZ.